Groove Pancreatitis. A Mini-Series Report and Review of the Literature - Manzelli, Antonio; Petrou, Athanasios; Lazzaro, Alesandra; Brennan, Nicholas; Soonawalla, Zahir; Friend, Peter (JOP. Journal of the Pancreas, 2011)
Context Groove pancreatitis is a rare condition characterized by fibrotic inflammation affecting the groove anatomical area between the head of the pancreas, the duodenum and the common bile duct. Objectives We report a miniseries of five cases treated surgically in our centre over a period of four years. A review of the literature is also discussed. Methods Patients undergoing pancreaticoduodenectomy over a four-year period were retrospectively reviewed. Patients with a confirmed histological diagnosis of groove pancreatitis were assessed under the headings; patient demographics, presenting symptoms, radiological and histological findings. Results One-hundred and 60 pancreaticoduodenectomies were performed. Thirty-nine cases demonstrated benign disease and within this, five cases (3.1% of total series; 12.8% of benign cases) were groove pancreatitis. All patients presented with abdominal pain and weight loss, and the majority consumed excess alcohol and were smokers. Radiological findings (CT/MRCP/EUS) revealed duodenal wall thickening in all cases, abnormalities at the head of pancreas and bile duct dilation in four, and cystic changes in the duodenal wall and pancreatic duct dilation in three cases. Groove fibrosis, Brunner’s gland hyperplasia and cystic changes in duodenal wall were present in all cases on histological review. All patients reported significant improvement in quality of life at 12 months after surgery. Conclusion Groove pancreatitis can present in a similar fashion to head of pancreas cancer and chronic pancreatitis. For this reason it is paramount for clinicians to be aware of groove pancreatitis, as this can lead to the correct diagnosis and management of this unique disease. Image: Ill-defined hypoechoic mass in the head of the pancreas at CECT.